1999
DOI: 10.1128/jvi.73.3.2410-2419.1999
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Addition of Poly(A) Tail and AU-Rich Sequences to the 3′ Terminus of the Sindbis Virus RNA Genome: a Novel 3′-End Repair Pathway

Abstract: Alphaviruses are mosquito-transmitted RNA viruses that cause important diseases in both humans and livestock. Sindbis virus (SIN), the type species of the alphavirus genus, carries a 11.7-kb positive-sense RNA genome which is capped at its 5′ end and polyadenylated at its 3′ end. The 3′ nontranslated region (3′NTR) of the SIN genome carries many AU-rich motifs, including a 19-nucleotide (nt) conserved element (3′CSE) and a poly(A) tail. This 3′CSE and the adjoining poly(A) tail are believed to regulate the syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 49 publications
0
27
0
Order By: Relevance
“…The TATase activity observed with the N-terminal truncated nsP4 was independent of other viral factors; however, a predilection towards viral RNA substrates was observed. Whether or not this is the genuine mechanism for viral polyadenylation is still unknown; evidence indicating the presence of a 59 poly(U) tract on the minus-strand RNA and the ability of truncated alphavirus genomic RNAs to be polyadenylated during infection highlight the complexity of viral polyadenylation (Hill et al, 1997;Raju et al, 1999;Sawicki & Gomatos, 1976). Purification of full-length nsP4 has been accomplished using an N-terminal SUMO tag method.…”
Section: Nsp4mentioning
confidence: 99%
See 1 more Smart Citation
“…The TATase activity observed with the N-terminal truncated nsP4 was independent of other viral factors; however, a predilection towards viral RNA substrates was observed. Whether or not this is the genuine mechanism for viral polyadenylation is still unknown; evidence indicating the presence of a 59 poly(U) tract on the minus-strand RNA and the ability of truncated alphavirus genomic RNAs to be polyadenylated during infection highlight the complexity of viral polyadenylation (Hill et al, 1997;Raju et al, 1999;Sawicki & Gomatos, 1976). Purification of full-length nsP4 has been accomplished using an N-terminal SUMO tag method.…”
Section: Nsp4mentioning
confidence: 99%
“…However, it is also possible that both a templated and non-templated mechanism of polyadenylation and terminal addition are at play during an alphavirus infection, allowing repair and restoration of infectivity of damaged or defective viral genomes. Further work by Raju and colleagues has found that, despite the essential nature of the 39 UTR, genomes lacking significant portions of this element are capable of producing progeny by a novel repair mechanism (George & Raju, 2000;James et al, 2007;Raju et al, 1999). Synthetic genomes with a set of deletions to the 39 CSE, UTR and/or poly(A) tail were introduced into cells, and viable progeny were recovered from many of these.…”
Section: Elementsmentioning
confidence: 99%
“…Various deletions and insertions in the 3= UTR as well as complete deletion of the poly(A) tail may not kill alphaviruses (457)(458)(459), flaviviruses (460)(461)(462), coronaviruses (463)(464)(465), and various plant viruses (466)(467)(468)(469). The repair of the damaged genomes may again involve different mechanisms, including RNA recombination, the use of the viral RdRP-or host-dependent polyadenylation activities, and perhaps some others.…”
Section: Some Additional Lessons From Other Rna Viruses Positive-stramentioning
confidence: 99%
“…Alphaviruses possess a highly conserved 3' sequence element (3' CSE; approximately 19 nt long) that immediately precedes the poly(A) tail [2]. Both the poly(A) tail and the 3'CSE are required for virus replication and, more specifically, for efficient minus-strand RNA synthesis [13][14][15][16][17]. The terminal 19 nt conserved sequence was identical in all GETV isolates, including the M1 isolate that was previously reported to have lost this conserved sequence [18,19].…”
Section: Pcr Amplification Sequence Analysis and Phylogenetic Compamentioning
confidence: 99%